POSTOPERATIVE PAIN MANAGEMENT IN DENTISTRY: A NARRATIVE REVIEW OF THE USE OF NONSTEROIDAL ANTI-INFLAMMATORY DRUGS - Dominika Domanowska,; Dominik Domoń,; Antoni Liebert,; Natalia Klimek,; Adam Niedziela,; Martyna Kaplińska,; Magdalena Nieroda,; Hanna Wilska, (International Journal of Innovative Technologies in Social Science, 2025)
Background. Postoperative pain is a frequent consequence of dental procedures and significantly affects patient comfort and recovery. The severity and duration of pain vary depending on the type of procedure and individual patient factors. Although it usually resolves within a few days, in some cases it may become chronic. Effective pain management is therefore essential.Aim. This review presents contemporary strategies for managing postoperative dental pain, with particular emphasis on the use and efficacy of nonsteroidal anti-inflammatory drugs (NSAIDs).Material and methods. A narrative review was conducted using PubMed and Google Scholar. Relevant peer-reviewed original articles, systematic reviews, and clinical trials published in English were selected. The inclusion criteria focused on studies concerning the use of NSAIDs in various dental disciplines, including conservative dentistry, pediatric dentistry, orthodontics, periodontology, prosthetics, and oral and maxillofacial surgery. Articles not related to dental postoperative pain or NSAID use, case reports, and expert opinions were excluded.Results. NSAIDs such as ibuprofen, ketoprofen, and selective COX-2 inhibitors have proven effective in reducing postoperative dental pain across a broad range of procedures. Their mechanism involves cyclooxygenase inhibition and modulation of inflammatory pathways. In many clinical scenarios, NSAIDs surpass opioids and paracetamol alone in efficacy. Preoperative administration is often beneficial, especially in pediatric and orthodontic cases. Additional non-pharmacological methods, such as cryotherapy and laser therapy, further enhance outcomes. However, gastrointestinal, renal, and cardiovascular risks must be considered.Conclusions. NSAIDs are fundamental in managing postoperative dental pain due to their anti-inflammatory and analgesic properties. The best outcomes are achieved through a personalized, multimodal approach combining NSAIDs with non-pharmacological strategies, ensuring effective pain relief while minimizing adverse effects.